Implementation of Pancasila Values in Scouting Activities (Case study at SMP Negeri 1 Mallusetasi Barru Regency) - Rismawati Rismawati; Muhajir K (JED (Jurnal Etika Demokrasi), 2020)
This study aims to determine how the implementation of Pancasila values in Scouting activities and what are the inhibiting factors and supporting factors for the Implementation of Pancasila values in Scouting activities. The benefits of this study use the theoretical benefits and practical benefits. This type of research is descriptive with a qualitative approach. Data collection techniques and data analysis techniques using interviews, and documentation. The results of this study indicate that: (1) The application of the divine value is evident from the observance of the members of the Boy Scouts in practising the teachings of Religion. The application of human values can be seen from the love between Scout members. Application of the value of unity seems to be carried out activities always prioritize to foster a sense of togetherness. The application of popular values can be seen from the preservation of democracy in scouting activities. Fairness values can be seen from the tolerance level of Scout members, as well as the Scoutmaster who is being fair. (2) Inhibiting factors lack of self-awareness to obey the rules, lack of cooperation in the task, the number of negative behaviours from outside. And Supporting Factors become more independent individuals, raise awareness, train discipline, learn Scout organizations well and train leadership, improve themselves to always apply the values of Pancasila such as diligently worshipping so that hearts and minds become calm.Keywords: Pancasila, the implementation of the values of Pancasila, ScoutingPenelitian ini bertujuan untuk mengetahui bagaimanakah Implementasi nilai-nilai pancasila dalam kegiatan Kepramukaan dan apa faktor penghambat dan faktor pendukung Implementasi nilai-nilai pancasila dalam kegiatan Kepramukaan. Manfaat penelitian ini menggunakan manfaat teoritis dan manfaat praktis. Jenis penelitian yang digunakan adalah deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dan teknik analisis data menggunakan wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa: (1) Penerapan nilai ketuhanan tampak terlihat dari ketaatanan aggota pramuka dalam mengamalkan ajaran-ajaran Agama. Penerapan nilai kemanusiaan tampak dari rasa kasih sayang antar anggota Pramuka. Penerapan nilai persatuan tampak kegiatan yang dilakukan selalu mengedepankan untuk memupuk rasa kebersamaan. Penerapan nilai kerakyatan tampak dari terjaganya demokrasi dalam kegiatan kepramukaan. Nilai Keadilan tampak dari tingkat toleransi anggota Pramuka, serta Pembina Pramuka yang bersikap adil. (2) Faktor Penghambat kurangnya kesadaran pada diri sendiri untuk patuh pada peraturan, kurangnya kerjasama dalam tugas, banyaknya perilaku negatif dari luar. Dan Faktor Pendukung menjadi pribadi yang lebih mandiri, meningkatkan kepedulian, melatih kedisiplinan, belajar organisasi Pramuka dengan baik dan melatih kepemimpinan, lebih membenahi diri untuk selalu menerapkan nilai-nilai Pancasila seperti rajin beribadah agar hati dan pikiran menjadi tenang.Kata kunci: Pancasila, implementasi nilai-nilai Pancasila, Kepramukaan.